Fluid-mediated selective dissolution of subducting carbonaceous material: Implications for carbon recycling and fluid fluxes at forearc depths - Vitale Brovarone, Alberto; Tumiati, Simone; Piccoli, Francesca; Ague, Jay J.; Connolly, James A.D.; Beyssac, Olivier (Chemical geology, 2020)
Subduction of crustal C governs the long-term global C cycling. The role of carbonates recycling in subduction zones and the related dissolution of C at various depths have been the subject of a large body of literature over the last decades. Much less is known about the contribution of carbonaceous material (CM) to the deep C cycling in subduction zones. This paper presents natural evidence for intense fluid-mediated leaching of CM in pelitic schists at high-pressure/low-temperature conditions relevant to the forearc region of subducting slabs. Manifestations of such process were identified along fluid pathways at various scales in the blueschist-facies subduction complexes of both Alpine Corsica and the Western Alps. Microstructural, whole-rock and Raman analyses across a selected metasomatic aureole were used to quantify the amount and mechanisms of C loss during fluid-rock interaction. In samples affected by intense fluid infiltration, >90% of the initial CM was removed from the rock. Microstructural and micro-Raman data indicate selective leaching of disordered CM relative to nearly crystalline graphite. The collected data allowed constraining the magnitude of fluid fluxes required to bleach the studied CM-bearing lithologies at different P-T-fO2 conditions, which corresponds to rather high time-integrated fluid fluxes in the order of ~106 m3/m2. In settings of large-scale fluid channelization, such as along regional-scale, lithological/tectonic boundaries or at the top of the subducted sedimentary pile, intense dissolution of subducted CM is expected. This process may thus exert a negative feedback on the sink of C phases into the deep mantle over the geological timescales and contribute to the release of isotopically light C from subducting slabs in forearc regions.